Approximation of equivalent source parameters change function by Franklin functions - Zhuikov, Valery; Osypenko, Kateryna (Publishing House of Lviv Polytechnic National University, 2016)
A problem of approximation of the primary energy flow parameters change function by linear approximations to ensure a minimal error is considered in the paper. A representation of the parameters of voltage and internal resistance of equivalent generators of renewable sources as linear functions allows an increase in the level of energy transmitted to the load. To solve the problem set, it is proposed to approximate the primary energy flow parameters change function by the system of Franklin orthonormal functions. It is shown that applying the m-shift operation to the Franklin orthogonal functions minimizes the error and the number of approximating functions. Розглянуто проблему апроксимації функції зміни параметрів потоку первинної енергії лінійними наближеннями із забезпеченням мінімальної похибки наближення. Подано параметри напруги та внутрішнього опору еквівалентних генераторів відновлюваних джерел лінійними функціями, яке дає змогу підвищити рівень енергії, що передається в навантаження. Запропоновано вирішення сформульованої проблеми через наближення функції зміни параметрів потоку первинної енергії системою ортонормованих функцій Франкліна. Показано, що застосування операції m-зсуву до ортогональних функцій Франкліна дає можливість мінімізувати похибку та кількість апроксимувальних функцій.
Апроксимація функції зміни параметрів еквівалентного джерела функціями Франкліна
Keywords: distributed generation; renewable energy sources; Heisenberg’s uncertainty principle; approximation; Franklin functions